Laparoscopic right hemicolectomy with complete mesocolic excision and D3 lymphadenectomy using the open book approach: a video vignette - Valentin Butnari; Ahmer Mansuri; Sultana Momotaz; Dixon Osilli; Richard Boulton; Joseph Huang; Nirooshun Rajendran; Sandeep Kaul (Journal of Minimally Invasive Surgery)
According to the concept of total mesorectal excision for rectal cancer, Hohenberger translated this concept to colonic cancer by introducing complete mesocolic excision (CME). The concept of this surgical technique was further elucidated by Benz et al. in the form of an open book approach. This article presents and demonstrates in a video a case of laparoscopic right hemicolectomy with CME and D3 lymphadenectomy using open book approach in the treatment of a T3N1M0 distal ascending colonic adenocarcinoma. The final pathology report confirmed moderately differentiated adenocarcinoma with a maximum tumor size of 55 mm and 0/60 lymph nodes. The mesocolic fascia was intact and R0 was achieved. The final staging was pT3pN0pM0. However, D3 lymphadenectomy is not universally adopted due to concerns of higher morbidity we believe that with adequate training and supervision CME with D3 LDN is feasible and safe to be offered to all right-sided colorectal cancers with curative intent treatment.